Analisis Proses Pembelajaran Selama Masa Endemi di SDI Perti Tomang - Sri Retnaningsih; Abdul Halim (Journal on Education, 2024)
This research uses a descriptive qualitative approach where the research is used to examine the condition of natural objects and the researcher is the key instrument. The research results show that the implementation of learning during the endemic period can run well even though previously there were changes in the implementation of learning due to the impact of the Covid-19 pandemic. As we know, teaching and learning activities are carried out in schools, however, it is different after Covid-19 occurred. To break the chain of spread of Covid-19, the Indonesian government issued a policy of limiting activities, including in the world of education. So the learning process during the Covid-19 pandemic is carried out online.